Melacak Warisan Muhammad Abduh: Tren Modernisasi Pendidikan Islam dari Al-Azhar ke Indonesia - Akhmad Ilman Nafia; Sa’adi Sa’adi; Muhammad Aji Nugroho (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
This article examines the thought of Muhammad Abduh, a central figure of modern Islamic reform,as a response to the intellectual stagnation and challenges of colonialism in the 19th century. The approachuses a conceptual-philosophical method with critical hermeneutic interpretative analysis of MuhammadAbduh's works textually, intertextually, and contextually. This article analyzes the philosophical foundations,implementation, and influence of Abduh's thought. The results show that Abduh's thought is built on threefundamental pillars: the integration of knowledge, critical rationality, and education as emancipation.Muhammad Abduh's thought is relevant to the views of realism, progressivism, reconstructionism, andreligious humanism, which emphasize an education that is puritanical, progressive, visionary, and glorifieshuman reason. His intellectual legacy has proven to be highly influential transnationally, especially inIndonesia, with the birth of modern Islamic educational institutions such as schools under the auspices ofMuhammadiyah, Al-Irsyad, and Persis. Muhammad Abduh's thought has strong implications forcontemporary Islamic education, particularly in the urgency of developing an integrative curriculum andcultivating critical (ijtihad) and scientific thinking as solutions to the problems of Indonesian Muslims.Keywords: Muhammad Abduh, Philosophy of Education, Islamic Modernism, Al-Azha